2003
DOI: 10.1080/1356182021000044120
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional perceptions of health care students

Abstract: Effective interprofessional working, which is widely considered as essential to high-quality health care, is influenced by the attitudes of health care professionals towards their own and other professional groups. Relatively little is known, however, about interprofessional attitudes, particularly of students in health care professions. This study aimed to increase our understanding of students' attitudes towards their own and other professional groups on entry to a programme of professional education. Hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
149
2
17

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(183 citation statements)
references
References 11 publications
15
149
2
17
Order By: Relevance
“…The validity and reliability of the RIPLS has been widely debated in the literature despite the tool being commonly used in research assessing IPE. A number of studies have reported the RIPLS as reliable and valid (Hind et al, 2003;Lawlis, Wicks, Jamieson, Haughey, & Grealish, 2016) and McFadyen et al (2005) reported an adequate internal consistency for three of the four subscales, warning that "roles and responsibilities" should be treated with caution.…”
Section: Data Collectionmentioning
confidence: 99%
“…The validity and reliability of the RIPLS has been widely debated in the literature despite the tool being commonly used in research assessing IPE. A number of studies have reported the RIPLS as reliable and valid (Hind et al, 2003;Lawlis, Wicks, Jamieson, Haughey, & Grealish, 2016) and McFadyen et al (2005) reported an adequate internal consistency for three of the four subscales, warning that "roles and responsibilities" should be treated with caution.…”
Section: Data Collectionmentioning
confidence: 99%
“…61 During the first years of a health sciences profession, it is theorized that within-group identification of social identity has not yet developed. Students see themselves as part of a much larger group (ie, first-year university students) rather than as pharmacy or medical students, 61 making IPE easier to initiate. Students are attracted to IPE to provide better patient care, enhance their future careers, and satisfy personal curiosity about other health care professions.…”
Section: Interprofessional Educationmentioning
confidence: 99%
“…If a broader definition of competencies is taken that includes student attitudes and knowledge, then several other instances in which competences have been incorporated into evaluations were found. For example, changes in students' attitudes or stereotypes were measured as an IPE learning outcome in several IPE evaluations (Hind et al 2003;Mandy, Milton & Mandy 2004;Hean et al 2006).…”
Section: Behaviourismmentioning
confidence: 99%